2014
DOI: 10.1063/1.4901178
|View full text |Cite
|
Sign up to set email alerts
|

Reduced lattice thermal conductivity in Bi-doped Mg2Si0.4Sn0.6

Abstract: This letter reports the thermoelectric properties of Bi-doped Mg2Si0.4Sn0.6 thermoelectric materials. It was found that the ZTs of this material could be greatly enhanced by Bi-doping. Analyses on the transport properties showed that the power factors of the material were enhanced while the lattice thermal conductivities were reduced by Bi-doping. The reduction of the lattice thermal conductivity was likely caused by the interstitial Bi impurities. A peak ZT ≈ 1.55 at 773 K was obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 21 publications
4
22
0
1
Order By: Relevance
“…Along with the increased PF for n-type conduction, the maximum ZT value we calculated is 1.75 at µ=0.22 eV corresponding to carrier concentration of 5.57 × 10 20 cm −3 . This enhanced ZT is in agreement with previous experiments that reported values of 1.55 (773 K), 43 1.2 (850 K) 44 and 1.4 (800 K) 45 for Mg 2.08 Si 0.37 Sn 0.6 Bi 0.03 , Mg 2 Si 0.57 Sn 0.4 Bi 0.03 and Mg 2. 16 Si 0.388 Sn 0.582 Bi 0.03 , respectively.…”
Section: A Stability and Electronic Structuresupporting
confidence: 93%
“…Along with the increased PF for n-type conduction, the maximum ZT value we calculated is 1.75 at µ=0.22 eV corresponding to carrier concentration of 5.57 × 10 20 cm −3 . This enhanced ZT is in agreement with previous experiments that reported values of 1.55 (773 K), 43 1.2 (850 K) 44 and 1.4 (800 K) 45 for Mg 2.08 Si 0.37 Sn 0.6 Bi 0.03 , Mg 2 Si 0.57 Sn 0.4 Bi 0.03 and Mg 2. 16 Si 0.388 Sn 0.582 Bi 0.03 , respectively.…”
Section: A Stability and Electronic Structuresupporting
confidence: 93%
“…A 400 keV beam of He 2+ ions and a detection angle of 107.5° was used for the detector. [14,15,16]. In addition to the Mg 2 Si phase, an elemental Mg phase is also observed, as indicated by the peaks at 36.59 o , 34.27 o and 32.15 o [17].…”
Section: Grazing Incidence X-ray Diffraction (Gixrd Rigaku Ultima IImentioning
confidence: 94%
“…The room temperature lattice thermal conductivity decreases as Mg excess increases in the range of 2.8 W•m -1 •K -1 to 2.5 W•m -1 •K -1 . It was reported that the bismuth interstitial can decrease the lattice thermal conductivity obviously in the Mg 2 (Si,Sn) ternary solid solution [8] . The decrease of the lattice thermal conductivity may be due to the Mg interstitials.…”
Section: Methodsmentioning
confidence: 98%